STRATEGIC ANALYSIS CASE STUDY: IHH HEALTHCARE BERHAD (Journal of Business Management and Accounting, 2026)
This paper conducts a strategic business analysis of IHH Healthcare Berhad, a global leader in the private healthcare sector, by integrating qualitative and quantitative tools. This case study examines the strategic position of IHH using a combination of qualitative and quantitative analysis based on secondary data sources, including IHH’s official annual reports, audited financial statements, industry reports, news articles, Bursa Malaysia Stock Exchange, and various financial websites. The findings suggest that IHH’s strong financial standing, diversified services, strategic acquisitions, and digital innovations are internal strengths, complemented by favourable macroeconomic and net positive landscapes as external strengths that position it well for sustained growth. The paper identifies regulatory constraints, medical talent shortages, and liquidity risks as ongoing challenges. IHH’s earnings peaked at RM20,660 million in 2023, generated significantly by earnings from Türkiye and Singapore. IHH shows an upward trajectory through revenue diversification, with improvements in profitability, rising EBITDA, sound debt management, and operational efficiency. IHH’s liquidity ratios are potential areas for improvement, but overall, they also point towards its healthy cash reserves. IHH is likely to continue to dominate the healthcare market share and earn solid returns. Four strategic options are proposed—expanding medical tourism and retirement services, vertical integration of supply chains, enhanced public–private partnerships, and investment in AI capabilities. Based on a QSPM model, medical tourism emerges as the most attractive strategy. This case offers valuable insights for business leaders, policymakers, and investors in healthcare strategy and transformation.
Keywords: IHH healthcare; strategic management; private healthcare; medical tourism; Malaysia